Karakterisasi Morfoekotipe dan Proksimat Pala Banda (Myristica fragrans Houtt.) - Ilyas Marzuki; M. R. Uluputty; Sandra A. Aziz; Memen Surahman (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2008)
A field research was conducted to study morpho-ecotype and proximate aspects of Banda nutmeg (Myristica fragrans Houtt.) in three ecotypes: Banda Islands, Ambon Island, and Ceram Island in Maluku. The objectives of the study were to characterize morpho-ecotype of the Banda nutmeg, to investigate the trees productivity across three ecotypes, and to identify the proximate characteristics of the fruit. Ten productive nutmeg sample trees aged ranging 25 to 50 years were chosen for observations. In morphological observation, 21 items were described based on IBPGR procedure, and then subjected to UPGMA cluster analysis. The proximates of nutmeg flesh including edible portion (EP), water content, protein content, fat content, and pectin content were analyzed by AOAC procedure. Morphological and proximate data were analyzed using SAS. Results show that Moluccas ecotypes characterized by hill and mountain has tectonic mountain physiography and karst soils with a slope of 16 to 40%. Ambon and Banda ecotypes are mainly composed of volcanic soils, whilst Luhu has sediment. The climate of Moluccas ecotype is dominated by IIIC type, except Banda Island which has IIB. The morphological traits of the nutmeg are stabile across three ecotypes (similarity index, SI 90%). Productions of fruit, nutmeg, and mace show no difference between the three sites. They are 137.73, 19.27, and 3.07 kg per tree, respectively. All proximate parameters analyzed are not statistically different, except EP. EP of Ambon ecotype is statistically different from that of Ceram but it is similar to Banda ecotype.